EFFECT OF CONTINUOUS TRAINING AND INTERVAL TRAININGON SELECTED VO2 MAXAMONG COLLEGE LEVEL MEN BOXERS - M.Girinathan, (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The objective of the present study is to identify the effects of continuous training and interval training performances on VO2 MAXamong college level boxers.Methodology: Twelve weeks of continuous trainingwas studied with constant-VO2 MAXprocedure and constant-time procedure. Twelve weeks of interval training was studied. ANCOVA statistical analyses have been used to analyses the performance and outcome of the men boxers and Scheffe’s post hoc test was used to find out the mean difference of confidence continuous training and Interval training. Result: The submaximal-performance effects on VO2 MAXF-ratio at 0.05 level of confidence for 2 and 87 (df) =3.06, 2 and 86 (df) =3.06. Significant is better than control group.